Mister world and his magical box Si ginoong mundo at ang kanyang mahiwagang kahon - Ayroso, Alelie Dew (Lampara books, 2013)
"Tatay Minggo has a job that brings him to different countries. he knows how to speak different languages and count various currencies. But the best part about his job is his homecoming every summer, bringing with him a magical box. But suddenly, one summer, he fails to come home, so there is no magical box. Find out in this story why Tatay Minggo was called Mister World, what the magical box contains, and most of all what friendship really means, especially in times of loss."